Electrospray drying for producing Active Pharmaceutical Ingredients (API) nanoparticles / Noor Fitrah Abu Bakar … [et al.] - Abu Bakar, Noor Fitrah; Naim, M Nazli; Abu Bakar, Mohd Rushdi; Zolkepali, Nurul Karimah (Research Innovation Business Unit, 2014)
Nanoparticles preparation of Mefenamic acid (MA) form I by using an electrospray drying method was conducted in this study. Mefenamic Acid (MA) is an anthranilic acid derivative and a non-steroidal anti-inflammatory drug. It is widely used in minor to moderate pain including headache, dental pain, postoperative and postpartum pain, dysmenorrhea, osteoarthritis. MA has two polymorphs, which is form I and II, and they also show different solubility and stability. To reduce size of MA, electrospray drying was used in this study. Electrospray drying is a process that uses electrostatic force to disperse a conductive liquid jet into fine charged droplets through the solvent evaporation and coulomb fission. When the solvent evaporation occurs, the mass of droplet will reduce and due to this condition the droplets becomes highly charged and is unstable. The instability of droplet forces it to disperse into small droplet and finally dry into fine particles and is deposited to the substrate. Depending on the strength of the electric stresses in the liquid, different spraying modes will be obtained which is dripping, pulsing, cone jet and multi jet and electrospray drying modes operation usually in cone jet mode. The prepared MA solutions with conductivity 2.77 µScm-1 and 8.55 µScm-1 for concentration 0.055 and 0.041 M respectively were placed inside 20 ml plastic syringe connected with stainless steel needle as a nozzle. Applicable solution conductivity for electrospray drying should be in the range of 1µScm-1 to 10 mScm-1 during the formation of stable cone jet mode. The solution was pumped at flow rate 3-6 ml h-1 through a 0.15 mm inside diameter needle by using a syringe pump. By applying the applied voltage at 1.3-1.5 kV with positive polarity and counter electrode with 7 mm diameter circular opening in the centre was positioned in perpendicular to the needle, cone jet mode was formed at the tip of needle prior to the electrospray drying. During electrospray drying process, solvent evaporation from the droplet was occurring that leads to coulomb disruption and may generate to nanoparticles. The dried nanoparticles were collected on a grounded substrate that was placed at varying distance which is 12 to 15 cm from the tip of needle. Electrospray drying under cone-jet mode can be used to produce nanosized particles in the range 100-400 nm. The electrospray process with cone jet mode was able to produce nanosized and monodisperse particle. The particle size was determined by the distance from tip to needle, at far distance, it was able to produce smaller particle than the particle at short distance due to repeated disruption. Characterization of particles by using X-ray diffractometry (XRD) and differential scanning calorimeter (DSC) show that reduction of particle size in the sample was indicated by low intensity and also low of melting behaviour respectively and there is no changes in polymorph and particles remain as form I. Using electrospray drying, will increase the surface- to-volume ratio by decreasing the product size and also offers a novel way to particles for drug formulation solving formulation problems of drugs with low solubility in class II of the Biopharmaceutical Classification System.